The Modern State : Theories and Ideologies - Cudworth, Erika (Edinburgh University Press, 2007)
Broad ranging in its coverage of the liberal democratic state and other, non-democratic state formations, the book offers chapters on each of the core theories of the modern state. Each chapter is structured in the same way to allow for ease of cross-referencing and for comparisons to be drawn between theories, with parts on Context, Definition, Theorists and Practical Politics.